Spike Shaped AMC Backed Patch Antenna for X Band Applications (International Journal of Innovative Research in Engineering & Management, 2022)
In This paper, a single pole broken spike  shaped antenna is there. The main objective is for the  application of WiMAX band. For the required band, we carried out the proposed antenna into different iteration  models. The proposed antenna which is heart shape works  in WiMAX Frequency (3.2GHz-4,1GHz). To Increase the  band width(900MHz), and gain (3dB), A two Slotted ring  resonator in heart shape is done in them last iteration. In  this design the parameters like VSWR is almost less than  the WiMAX band and impedance will be 89% has been  noted. Finallly the monopole antenna which in broken  heart shape works at WiMAX band having medium gain,  high efficiency, reduce in size that are useful for WiMAX  band applications
Keywords: VSWR; SRR (Slotted ring resonator); Borken heart shaped antenna; WiMAX